PELATIHAN BUDIDAYA (Daphnia sp.) UNTUK PAKAN ALAMI SEBAGAI LAPANGAN PEKERJAAN POTENSIAL BAGI KELOMPOK PEMUDA DESA PAYA BUJOK SEULEUMAK, KOTA LANGSA - Putri, Kartika Aprilia; Rahmawati, Rahmawati; Febri, Suri Purnama; Yusman Persada, Andri; Haser, Teuku Fadlon (Universitas Muhammadiyah Tapanuli Selatan, 2022)
This community service activity aims to train the community, especially youth groups in the village of Paya Bujok Seuleumak in the cultivation of Daphnia sp. for natural betta fish feed by utilizing chicken manure waste as an alternative potential employment. The training activity was carried out for 3 times and was attended by 20 participants. The participants of the activity were creative youths in the village of Paya Bujok Seuleumak, Langsa City, Aceh. The method used in this activity is the direct approach method, practice, and lectures. The results achieved in this activity are the cultivation of natural feed (Daphnia sp.) using chicken manure which can increase economic value. From the results of post-activity monitoring and evaluation, it is known that all participants can apply and re-apply independently and can produce their own Daphnia sp., so as to get optimal results.